The Influence of a High-Order Thinking (HOTS)-based Learning Model on Students' Midterm Question Analysis - Indah Purnama Sari; Tengku Aldy Hatta; Asrar Aspia Manurung; Surya Wisada Dachi; Tua Halomoan Harahap; Zainal Azis; Ahmad Riady Hasibuan (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
This research aims to determine the cognitive level categorization of the Revised Bloom's Taxonomy on Indonesian language and literature UTS questions for classes X, XI, The 2020/2021 academic year at SMA Muhammadiyah 18 Sunggal contains higher order thinking skills. The sample used in this research is UTS questions for Indonesian language subjects from classes X to XII. The research method used is descriptive survey research. Data sources were taken from each class, each class consisting of 30 questions. Data analysis techniques use Milles and Huberman, namely data collection, data reduction, data presentation, drawing conclusions. The research results from class In class In class In class In class In class XII even semester, the categories are Lost 7%, Most 0%, Hots 93%. This shows that the question is included in the hots question.